A robust sharp interface method for SPH. (September 2019) - Zhang, Mingyu; Deng, Xiao-Long; Shen, Zhijun
Abstract: Based on our previous sharp interface method (SIM) for smoothed particle hydrodynamics (SPH) [Zhang M and Deng X-L. A sharp interface method for SPH. Journal of Computational Physics 2015; 302 469–484], a robust SIM for SPH is developed. According to Lagrangian nature of SPH, the interface is located between two types of SPH particles. It is different from the previous method, in which the initial interface is defined by the user. The main consequence of the interface definition in the current method is that minimum value of level set function is around half the initial inter-particle distance. Therefore the calculation of level set function becomes more robust. The interface status is determined by jump conditions at the interface. Then the interface status is extended to the ghost fluid particles. Various benchmark tests are given to show the performance of the robust SIM for SPH. Comparing with the previous SIM for SPH, current method is more robust and accurate in the simulation of low-speed multiphase flows of high density ratios with clear interface.